Analisis Delik Culpa dan Pertanggungjawaban Pidana atas Kelalaian Pejabat Negara dalam Perkara Korupsi melalui Studi Putusan 68/Pid.Sus-TPK/2025/PN Jkt Pst. - Dian Rusmana; Numan Sofari Hafid; Syahrul Anwar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study seeks to unravel the complexities of applying the doctrine of culpa lata or gross negligence as the basis for criminal liability for state officials in corruption cases, an area that highlights gaps in the criminal law framework which tends to focus on intent. With the rise in corruption cases stemming from misguided strategic decisions that are difficult to prove as intentional, the urgency to explore alternative criminal liability grounds becomes crucial for establishing strong accountability in governance. This research specifically analyzes the application of culpa lata through an in-depth study of Decision Number 68/Pid.Sus-TPK/2025/PN Jkt Pst. Adopting a normative-empirical qualitative case study method, the analysis focuses on the court decision as a single unit of analysis, supported by primary data from the decision document and secondary data from legal literature. Through documentary evidence tracking, it was found that the panel of judges successfully applied the doctrine of culpa lata by identifying elements of negligence such as the disregard for risks that should have been known, subjective asset valuation, and strategic decision-making without adequate study, which causally led to state losses. These findings substantively show that gross negligence can effectively serve as a basis for criminal liability, indicating a shift in the pattern of corruption law enforcement that goes beyond proving mere intent. In conclusion, this study affirms the effectiveness of culpa lata in expanding the scope of criminal liability for state officials, offering theoretical contributions to the understanding of fault elements and practical implications in strengthening public accountability and the potential for corruption prevention through enhanced standards of caution.